The Prevalence and Associated Risk Factors of Children With Reading Disabilities in a Multiethnic City: A Cross-Sectional Study - Feng, Yanan; Liu, Qi; Xie, Xinyan; Jiang, Qi; Zhu, Kaiheng; Xiao, Pei; Wu, Xiaoqian; Zuo, Pengxiang; Song, Ranran (Frontiers in Pediatrics, 2022)
Numerous studies have been conducted to explore the risk factors for reading disabilities among children. Based on these studies, factors such as gender, socioeconomic status, and the home literacy environment have been widely found to be associated with children who have reading disabilities. However, children from a multi-ethnic city are seldom investigated. The current study aimed to explore the prevalence of reading disabilities and the potential environmental risk factors in Shihezi, Xinjiang, where people of multiple ethnicities, including Han and ethnic minority children, live and study together. A cross-sectional study was conducted in the city of Shihezi. A two-stage sampling strategy was applied to randomly select six primary schools in the city. In total, 6539 students in grades two to six participated in the study. There were 6065 valid questionnaires obtained for further analyses. We used the Dyslexia Checklist for Chinese Children and the Pupil Rating Scale to screen for the children with reading disabilities. The χ2 test and multivariate logistic regression were employed to reveal the potential risk factors of reading disabilities. The prevalence of children with reading disabilities was 3.38% in Shihezi city and was significantly different between Han (3.28%) and Uighur (7.42%) children (P < 0.05). There was no significant difference in the prevalence of reading disabilities between Han and Hui children. Among these children with reading disabilities, the gender ratio of boys to girls was nearly 2:1. Multiple logistic regression analysis showed that gender (P < 0.01), learning habits (P < 0.01), and the home literacy environment (P < 0.01) were associated with RD. The results may be useful in the early identification and intervention of children with reading disabilities, especially among ethnic minorities.